Методи побудови узагальнених ретрактів - Pyrch, N. M.; Національний університет «Львівська політехніка», Львів (Pidstryhach Institute for Applied Problems of Mechanics and Mathematics of NAS of Ukraine, 2024)
We consider structures and functors for constructing examples of the generalized retracts concerned with the extensions of the continuous mappings into topological groups. Cite as: N. M. Pyrch, “Methods for constructing generalized retracts,” Prykl. Probl. Mekh. Mat., Issue 22, 13–30 (2024) (in Ukrainian), https://doi.org/10.15407/apmm2024.22.13-30